Effect of Corruption, Income Inequality, and Unemployment on Poverty in Context of Nepal - Bijukchhen, Suban; Phaju, Rajan (Khwopa Journal, 2023)
The aim of this study is to look into the connections between unemployment, economic inequality, and poverty in Nepal. In the study, variables including absolute poverty, CPI index score, Gini coefficient, and unemployment are used with data from 2000 to 2020. The Toda Yamamoto test was used in the study to determine whether the variables were causally related because not all data were stationary, even at the second difference. Additionally, the stability was evaluated using a cointegration test, and the normalcy test was observed using a descriptive analysis. According to the study's findings, poverty in Nepal is significantly influenced by corruption, income inequality, and unemployment. The variables are found to have a direct or indirect correlation with one another. Therefore, the study comes to the conclusion that preventing poverty in Nepal would be difficult without reducing corruption, economic disparity, and unemployment. Policymakers may find the findings helpful in creating plans to combat poverty and advance the nation's economy.